Effects of memantine and clopidogrel alone and in combination in a cerebral ischemia-reperfusion model - Özdemir, Hasan Hüseyin; Ilhan, Selçuk; Demir, Caner F.; Akgün, Bekir; Kapan, Oktay; Ataş, Eser; Balduz, Metin (Elsevier B.V., 2015)
There are many factors in cerebral ischemia that cause cell death. Glutamate receptor-mediated neurotoxicity is the major mechanism involved in hypoxic-ischemic brain injury (HIBI). Memantine is a low affinity, non-competitive NMDA antagonist blocker, while clopidogrel is an antiplatelet agent used in the treatment of ischemic stroke. The aim of this study is to investigate the effects of clopidogrel and memantine (alone and in combination) on HIBI. Thirty-five Sprague-Dawley rats were exposed to hypoxia for 10 min by ligation of the bilateral common carotid artery. Following this, the rats were divided equally into groups as follows: control, ischemia, memantine (IM), clopidogrel (IC) and memantine + clopidogrel (IMC). Drug therapy was administered for a period of five days, after which all rats were sacrificed and malondialdehyde (MDA), total antioxidant status (TAS), total oxidant (TOS) values, and oxidative stress index (OSI) were determined in brain tissue. MDA and TOS values were significantly higher in the group that underwent ischemia than in the control group. MDA, TOS and OSI values were significantly lower in the groups treated with IM, IC, or IMC than in the group that underwent ischemia. Although it was not significant, TOS and OSI were lower in the groups that underwent combined treatment than in the groups that underwent treatment with IM or IC alone. Our results indicate that memantine and clopidogrel treatment, when used individually, reduce oxidative stress in HIBH more so than when these treatments are combined. This may be due to potential pharmacokinetic mechanisms of the combined therapy. © 2014 Elsevier GmbH. All rights reserved.
Keywords: Cerebral ischemia; Clopidogrel; Memantine; Rat